Analisis Kinerja Keuangan Dari Segi Likuiditas, Solvabilitas, Dan Profitabilitas Pada Perusahaan Manufaktur - Anggita, Ersalina Septya; , Edipurwo Saputro, S.E,. M.Si (2016)
This study aims to determine the financial performance. Ace Hardware Indonesia Tbk tend to go up or down and analyze financial performance during 2012, 2013 and 2014. The data used in this study a document obtained from the internet relating to historical financial data of PT. Ace Hardware Indonesia Tbk. The results of this study are expected to provide information about the financial position of the company for consideration in making policy and strategy of the company in improving its financial performance. The ratio used is the liquidity ratio, solvency and profitability ratios. The results of the study in terms of the ratio of liquidity consisting of current ratio, cash ratio and quick ratio shows that PT. Ace Hardware Indonesia Tbk in a state quite illiquid due to the increase in current assets. Based Solvency ratio consisting of debt to asset ratio and debt-to-equity ratio shows that PT. Ace Hardware Indonesia Tbk is in fairly good condition due to increased equity. Based Profitability ratios PT. Ace Hardware Indonesia Tbk has not said to be good because of the profit generated decreases.